Empowering Program as a Special Service for the Poor Parents of Children with Special Needs (CSN) - Ardiana Meilinawati (The Center for Disability Studies and Services Brawijaya University, 2019)
Children with special needs (CSN) are individuals who are under 18 years or older whose mental condition is under 18 years and have growth and development problems that require special services, the Government has provided several facilities for CSN as a form of empowerment. However, these services have not yet led to the empowerment of CSN through education on public awareness to understand the needs and potential of CSN. Therefore, an empowerment program through parents is needed as a significant other of CSN. The purpose of this study is to find out the picture if the CSN parent empowerment program is carried out. The method used is through a qualitative approach and action research. The results showed that the CSN parent empowerment program needs to collaborate with various parties by growing trust in CSN parents to maintain commitment in participating in the program.